IMPROVING CRITICAL THINKING SKILL THROUGH GUIDED INQUIRY LEARNING MODEL USING MULTIMEDIA IN THE LEARNING OF IPA ABOUT FORCE FOR THE THIRD GRADE STUDENTS OF SD NEGERI 1 MANGUNWENI IN THE ACADEMIC YEAR OF 2016/2017. - aminah, siti; susiani, tri saptuti; suryandari, kartika chrysti (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: Improving Critical Thinking Skill through Guided Inquiry Learning Model using Multimedia in the Learning of IPA about Force for the Third Grade Students of SD Negeri 1 Mangunweni in the Academic Year of 2016/2017. The objective of this research is to improve critical thinking skill and students? learning outcome of IPA about force. This research is a collaborative Classroom Action Research (CAR) conducted within two cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were teacher and third grade students of SD Negeri 1 Mangunweni.  Techniques of collecting data were learning outcomes test, observation, and interview. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptiveanalysis consisting of data reduction, data display, and drawing conclusion or verification. The results of this research show that the use of guided inquiry learning model using multimedia can improve critical thinking skill and students? learning outcome of IPA about force.Keywords: Guided Inquiry, multimedia, Critical thinking, Learning outcome, IPA